Calculation methods power generation of the laser beam - Левицький, Сергій Миколойович (Science-based technologies, 2020)
The choice of a laser for carrying out a technological operation is determined by the specifics of the effect of laser radiation on this material and the features of the assigned technological task. The main parameters characterizing laser radiation are power, radiation wavelength, radiation exposure duration, energy and pulse repetition rate, as well as coherence, directivity, monochromaticity and polarization of radiation. Most laser technologies are based on the thermal effect of radiation, that is, it is assumed that the object to be heated must be heated to a given temperature. Therefore, the main characteristic of the laser used in such technologies is its power. For pulsed lasers, the power in a pulse and the average power, which depends on the duration and pulse repetition rate, are considered. In this work, we calculated the power of the laser beam generation depending on the design of the oprichnina quantum generator. The analysis is carried out depending on the parameters of laser irradiation, especially on the design of laser generators, that is, on the layout and placement of elements of an optical quantum generator. To achieve maximum laser efficiency, it is necessary to create such a resonator design and the shape of the active medium that allow their volumes to be combined in the best way when the fraction of the upper laser level dispersion as a result of spontaneous and relaxation transitions decreases and the fraction of stimulated transitions increases. As a result of optimizing the parameters of the optical generator, the radiation energy density reaches high, striking values through a small beam size. The beam, spreading, changes slightly due to small divergence, respectively, there is a risk of damage even at a great distance. Moreover, in the case of the propagation of invisible radiation, the presence of danger may not be obvious, and even visible radiation will be noticeable in the air only in the presence of suspended particles.